Device and method for studying the influence of surrounding rock fissure water on the erosion process of buffer materials
By manually cutting the cracks in the rock or using cores with natural cracks, combined with pressure/volume controllers and pure water/solution converters, the erosion process of surrounding rock crack water on buffer materials is solved, and it is difficult to accurately simulate in the prior art. The problem of this process achieves the accuracy and reliability of experimental results.
Patent Information
- Application Number
- CN202110093042.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-01-25
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2041-01-25
AI Technical Summary
The prior art is difficult to effectively simulate and study the impact of surrounding rock fracture water on buffer material erosion process, especially in complex rock fracture environments, which are difficult to accurately reflect the actual conditions on site.
By manually cutting out cracks with known openings in the complete rock, or using cores with natural cracks, combined with pressure/volume controllers, pure water/solution converters and pressurized structures, the erosion process of water flow on buffer materials is simulated. And collect and analyze the erosion liquid by recycling structures.
It realizes the erosion process of surrounding rock crack water on buffer materials under relatively simple experimental conditions, providing accurate and reliable experimental results, and provides scientific basis for the design of large-scale on-site experiments and the selection of buffer materials.
Smart Images

Figure CN112858157B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of surrounding rock fissure research, and in particular to a device and method for studying the influence of surrounding rock fissure water on the erosion process of buffer materials. Background Art
[0002] As an important component of the geological repository for high-level radioactive waste, one of the important functions of the buffer material bentonite is to seal the cracks in the surrounding rock. However, due to the influence of the friction force on the side walls of the cracks, the density of the bentonite that expands and squeezes into the cracks in the surrounding rock decreases with the increase of the squeezed distance, and interacts with the groundwater in the cracks to form a looser bentonite gel, and even free bentonite colloid particles appear. When the shear force of the groundwater flow exceeds the anti-erosion capacity of the bentonite gel / colloid particles, the bentonite particles will be carried away by the groundwater and leak along the cracks in the surrounding rock.
[0003] Using real granite fissures to reproduce the blocking of cracks by buffer materials and the subsequent erosion process can undoubtedly best reflect the actual situation of the interaction between buffer materials and surrounding rocks in waste disposal units. However, due to the complexity of rock fissures themselves and the difficulty of sample processing and experimental device design and development, such experiments are rarely reported. Using large-scale rock blocks for experiments can easily determine the crack morphology using optical means, and the difficulty of sample and device processing is relatively low compared to small cracks, but it is more difficult to achieve the blocking and accurate measurement of water flow. Therefore, it is necessary to make certain compromises on the test conditions, using the simplest technical means possible to simulate the erosion of buffer materials by water in the surrounding rock fissures of the disposal repository, while being able to restore the actual boundary conditions on site as realistically as possible, so that the results of indoor tests are accurate and reliable, providing a scientific basis for the design of large-scale field tests and the selection of buffer materials. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a device and method for studying the influence of surrounding rock fissure water on the erosion process of buffer materials. By artificially cutting fissures of known openings in intact rocks, or selecting cores with natural fissures, the expansion and fissure-sealing performance and anti-erosion performance of bentonite under the action of fissure water are studied.
[0005] To achieve the above object, the present invention provides the following solutions:
[0006] The present invention provides a device for studying the influence of surrounding rock fissure water on the erosion process of buffer materials, comprising a pressure / volume controller, a pure water / solution converter, a test core, a pressurizing structure and a recovery structure; a buffer material sample is arranged in the test core, the test core is arranged in the pressurizing structure, one end of the pure water / solution converter is connected to the pressure / volume controller, the other end of the pure water / solution converter is connected to one end of the test core, and the recovery structure is used to recover the solution flowing out of the other end of the test core.
[0007] Optionally, the test core includes rock, a block, a permeable pad and a sealing sleeve; a crack with a known opening is provided at one end of the rock, and a hollow cavity is provided at the other end of the rock, the crack is connected to the hollow cavity, the buffer material sample is arranged in the hollow cavity, and the block is arranged at the end of the hollow cavity away from the crack; a permeable pad is provided at each end of the rock, and the sealing sleeve is arranged on the outside of the rock; one end of the pure water / solution converter is connected to the permeable pad close to the block; the recovery structure is connected to the permeable pad close to the crack.
[0008] Optionally, the pressurized structure includes a sealed shell, an air supply mechanism, a left base and a right base; the left base is arranged on the left side wall inside the sealed shell, and the right base is connected to the left base by bolts; the test core is arranged between the left base and the right base; the air supply mechanism is connected to the interior of the sealed shell.
[0009] Optionally, a pressure gauge is provided on the sealed housing.
[0010] Optionally, a safety valve is provided on the sealed housing.
[0011] Optionally, the gas supply mechanism includes a nitrogen cylinder.
[0012] Optionally, the buffer material sample is a sodium bentonite block with a water content of 15% and a density of 1.6 g / cm 3 .
[0013] Optionally, the recovery structure includes a liquid collecting bottle.
[0014] Optionally, the pure water / solution converter includes a top cover, a base, a water tank and a water-proof membrane; the water tank is arranged between the top cover and the base, the water-proof membrane is arranged in the middle of the water tank, the top cover is provided with an exhaust hole and a water outlet hole, the base is provided with a water inlet hole, the water inlet hole is connected to the pressure / volume controller, and the water outlet hole is connected to the test core.
[0015] The present invention also discloses a method for studying the influence of surrounding rock fissure water on the erosion process of buffer materials, which mainly comprises the following steps:
[0016] The first step is to select a granite core with obvious cracks running through it along the length, cut off 10 cm, and drill a hole from one end with a diameter of 3 cm and a depth of 6.5 cm; or, select a complete core, cut off 10 cm, drill a φ3 cm × 6.5 cm hollow cavity in the middle, and then cut it into two identical parts along the length;
[0017] In the second step, a 3D laser scanner is used to obtain the surface morphology of natural / artificial fractures;
[0018] The third step is to weigh sodium bentonite powder with a moisture content of 15% and use a special compaction mold on a press to prepare a φ3cm×3cm cylindrical bentonite block with a dry density of 1.6g / cm 3 ; Place bentonite blocks into the hollow cavity in the core and use granite blocks to fill the space above the core;
[0019] Step 4: Open the sealing shell, put the sealing sleeve on the outer surface of the core, and use cable ties to fix the two ends of the sealing sleeve to the top of the left base and the right base; fix the left base and the right base to the test chamber with stainless steel bolts; assemble the sealing shell and seal it;
[0020] The fifth step is to connect the air supply mechanism and the sealing shell, inflate and check the airtightness of the connecting pipeline and the sealing shell. If leakage is found, it should be dealt with in time; increase the air pressure inside the sealing shell to no less than 4000kPa, so that the sealing sleeve is close to the outer surface of the rock;
[0021] Step 6. Open the vent of the pure water / solution converter, use a peristaltic pump or syringe to inject the test solution into the upper water tank through the water outlet until the test solution overflows the vent, and then close the vent.
[0022] Step 7: operate the pressure / volume controller to absorb pure water, connect the pressure / volume controller, the pure water solution converter, the pressurizing mechanism, and connect the pressurizing mechanism with the recovery mechanism;
[0023] Step 8: Use a pressure / volume controller to pressurize the test solution into the test core through the outlet of the pure water / solution converter, with the water flow rate ranging from 0.01 to 1 mL / min; continuously record the water pressure changes during the test;
[0024] Step 9: Replace the liquid collection bottle every 24 hours; shake the collected erosion liquid evenly, measure the turbidity, conductivity, and pH value, and then dry it at 105°C to constant weight;
[0025] Step 10: When the turbidity of the corrosion liquid measured within 72 hours is less than 0.1 NTU, the test is considered to have reached equilibrium and the liquid injection is terminated; the air pressure in the sealed shell is reduced to atmospheric pressure and the sealed shell is opened;
[0026] Step 11: Open the core to measure the depth of bentonite squeezed into the cracks, and scan the crack surface morphology again to compare with that before the test;
[0027] The twelfth step is to analyze the relationship between water flow velocity, water pressure, crack morphology and the distance and erosion amount of bentonite extruded into the crack, so as to understand the sealing and anti-erosion performance parameters of sodium-based bentonite under the conditions of water erosion in granite cracks.
[0028] Compared with the prior art, the present invention has achieved the following technical effects:
[0029] The device and method for studying the influence of surrounding rock fissure water on the erosion process of buffer materials in the present invention use rocks with natural fissures, or complete rocks with processed fissures, and confine cylindrical bentonite samples inside the rock samples, which reflects the structure in the actual disposal pit as realistically as possible. It is a miniature disposal pit structure and can simulate the situation of bentonite swelling to block the fissures and erosion when there is water flowing through the fissures; the bentonite sample and the rock as a whole are placed in a pressurizing mechanism and a high air pressure is applied, so that the test solution can only flow along the fissures, thereby linking the bentonite blocking fissures and erosion related parameters with the fissure surface parameters, solving the problem that the relationship between these two groups of variables cannot be directly studied in such experiments. This problem; at the same time, based on a large number of tests, the air pressure value in the pressurizing mechanism is proposed, so that the surface parameters of the cracks will not change due to the influence of the swelling force of bentonite, and the test parameters can be accurately controlled; the pressure / volume controller is used to provide water flow for the test, and the change of water pressure in the test system can be recorded, and the change of water pressure can be linked to the relevant information of bentonite entering the cracks; the pure water / solution converter is creatively applied, which greatly expands the types of test solutions, and can study the effects of corrosive solutions such as acids and alkalis, and special solutions with high salinity, heavy metals, and radioactive substances on bentonite erosion; based on a large number of test results, quantitative conditions for test balance are proposed. In summary, the device and method for studying the influence of surrounding rock fissure water on the erosion process of buffer materials in the present invention use simple and easy-to-operate technical means to simulate the erosion of buffer materials by surrounding rock fissure water in the disposal repository, and at the same time can restore the actual boundary conditions on site as realistically as possible, so that the test results are accurate and reliable. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0031] Figure 1 It is a schematic diagram of the structure of the device for studying the influence of surrounding rock fissure water on the erosion process of buffer materials according to the present invention;
[0032] Figure 2 The present invention is a schematic diagram of the structure of the device for studying the influence of surrounding rock fissure water on the erosion process of buffer materials in use.
[0033] Explanation of the reference numerals in the accompanying drawings: 1. Pressure / volume controller; 2. Pure water / solution converter; 3. Nitrogen bottle; 4. Liquid collecting bottle; 5. Water-permeable pad; 6. Bentonite block; 7. Sealing sleeve; 8. Pressure gauge; 9. Left base; 10. Right base; 11. Safety valve; 12. Crack; 13. Rock; 14. Block; 21. Fastening screw; 22. Exhaust hole; 23. Top cover; 24. Water outlet; 25. Upper water tank; 26. Water-proof membrane; 27. Lower water tank; 28. Base; 29. Water inlet; 210. Support seat. DETAILED DESCRIPTION
[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] Embodiment 1:
[0036] like Figure 1 and 2 As shown, this embodiment provides a device for studying the influence of surrounding rock fissure water on the erosion process of buffer materials, including a pressure / volume controller 1, a pure water / solution converter 2, a test core, a pressurization structure and a recovery structure; the buffer material sample is arranged in the test core, the test core is arranged in the pressurization structure, one end of the pure water / solution converter 2 is connected to the pressure / volume controller 1, and the other end of the pure water / solution converter 2 is connected to one end of the test core, and the recovery structure is used to recover the solution flowing out of the other end of the test core.
[0037] In this specific embodiment, the test core includes rock 13, block 14, water-permeable pad 5 and sealing sleeve 7; a fissure 12 with a known opening is provided at one end of the rock 13, a hollow cavity is provided at the other end of the rock 13, the fissure 12 is connected to the hollow cavity, the buffer material sample is provided in the hollow cavity, the block 14 is provided at one end of the hollow cavity away from the fissure 12; a water-permeable pad 5 is provided at each end of the rock 13, and the sealing sleeve 7 is provided outside the rock 13; one end of the pure water / solution converter 2 is connected to the water-permeable pad 5 near the block 14; the recovery structure is connected to the water-permeable pad 5 near the fissure 12. The water-permeable pad 5 is a porous stainless steel plate.
[0038] The pressurized structure includes a sealed shell, an air supply mechanism, a left base 9 and a right base 10; the left base 9 is arranged on the left side wall inside the sealed shell, and the right base 10 is connected to the left base 9 by bolts; the test core is arranged between the left base 9 and the right base 10; the air supply mechanism is connected to the inside of the sealed shell.
[0039] The sealed housing is provided with a pressure gauge 8. The sealed housing is provided with a safety valve 11.
[0040] The gas supply mechanism includes a nitrogen bottle 3. The nitrogen bottle 3 provides a pressure of not less than 4000 kPa inside the test cavity and maintains it during the test. Its function is to ensure that the sealing sleeve 7 wrapped around the outer surface of the granite is tightly attached to the outer surface of the granite, so that the liquid pumped in during the test cannot flow along the granite surface, but all flows along the cracks 12, so that the properties of the liquid, such as the relationship between flow rate, flow rate, chemical composition, etc. and erosion, can be studied. The air pressure of not less than 4000 kPa is selected, that is, the expansion force generated by the compacted bentonite sample under the density conditions selected in the test after contacting water is not enough to open the granite cracks 12 and change the parameters of the cracks 12. The air pressure value can be manually adjusted through the valve and pressure gauge on the nitrogen bottle 3, and can also be connected to an automatic air pressure regulating device. Due to the high pressure, a pressure gauge 8 and a safety valve 11 are installed on the sealed shell. The indication on the pressure gauge 8 is compared with the pressure gauge 8 on the nitrogen bottle 3 to evaluate whether the system has air leakage; and the safety valve 11 automatically deflates when the system pressure is greater than the set value. The air supply mechanism can be replaced by using a hydraulic pump to pump in water pressure or oil pressure.
[0041] The buffer material sample is a sodium bentonite block 6, which has a water content of 15% and a density of 1.6 g / cm 3 .
[0042] The recovery structure comprises a liquid collecting bottle 4 .
[0043] The pure water / solution converter 2 includes a top cover 23, a base 28, a water tank and a water-proof membrane 26; the water tank is arranged between the top cover 23 and the base 28, the water-proof membrane 26 is arranged in the middle of the water tank, the top cover 23 is provided with an exhaust hole 22 and a water outlet 24, the base 28 is provided with a water inlet 29, the water inlet 29 is connected to the pressure / volume controller 1, and the water outlet 24 is connected to the test core. The pressure / volume controller 1 can accurately control the flow rate of the pumped liquid and automatically record its pressure. Because it is a precision instrument, distilled water is generally required to avoid the precipitation of particles or other impurities in the water affecting its accuracy. When using acidic, alkaline or high-salinity liquids as test media, a pure water / solution converter is required.
[0044] The pure water / solution converter is used in conjunction with the pressure / volume controller 1 to provide a source of liquid inlet for the test cavity. The water-proof membrane 26 is a flexible diaphragm made of acid- and alkali-resistant Teflon material. The diaphragm separates two liquids, one is the pure water (distilled water / deionized water) from the pressure / volume controller 1, and the other is the test solution. When the pressure / volume controller 1 pumps water at a certain flow rate, the diaphragm deforms and pushes the test solution into the test cavity. In essence, it is a protective device for the pressure / volume controller 1, and can be extended to geotechnical tests under a variety of solution conditions (in addition to acids, alkalis, and salts, contaminated water containing heavy metal ions, radioactive substances, etc.).
[0045] Embodiment 2:
[0046] This embodiment discloses a method for studying the influence of surrounding rock fissure water on the erosion process of buffer materials in the first embodiment, which mainly includes the following steps:
[0047] The first step is to select a granite core with obvious cracks running through it along the length direction, cut off 10 cm, and drill a hole from one end with a diameter of 3 cm and a depth of 6.5 cm; or, select a complete core, cut off 10 cm, drill a φ3 cm×6.5 cm hollow cavity in the middle, and then cut it into two identical parts along the length direction. After adding water in the subsequent steps, the water flow cannot flow along the outer surface of the rock but flows entirely through the cracks. At the same time, the expansion force generated by the bentonite block 6 after contacting water does not change the opening of the cracks because it is much smaller than the external air pressure;
[0048] In the second step, a 3D laser scanner is used to obtain the surface morphology of natural / artificial fractures;
[0049] In the third step, sodium bentonite powder with a water content of 15% was weighed and a φ3 cm×3 cm cylindrical bentonite block 6 was prepared on a press using a special compaction mold with a dry density of 1.6 g / cm 3 ; Place the bentonite block 6 into the hollow cavity in the core, and use the granite block 14 to fill the gap above the core;
[0050] Step 4: open the sealing shell, put the sealing sleeve 7 on the outer surface of the core, and use cable ties to fix the two ends of the sealing sleeve 7 to the top of the left base 9 and the right base 10; fix the left base 9 and the right base 10 to the test chamber with stainless steel bolts; assemble the sealing shell and seal it;
[0051] The fifth step is to connect the air supply mechanism and the sealing shell, inflate and check the airtightness of the connecting pipeline and the sealing shell, and deal with it in time if leakage is found; increase the air pressure inside the sealing shell to not less than 4000 kPa, so that the sealing sleeve is close to the outer surface of the rock 13;
[0052] Step 6: Open the vent 22 of the pure water / solution converter 2, use a peristaltic pump or a syringe to inject the test solution into the upper water tank 25 through the water outlet until the test solution overflows the vent 22, and then close the vent 22;
[0053] Step 7: operate the pressure / volume controller 1 to absorb pure water, connect the pressure / volume controller 1, the pure water / solution converter 2, the pressurizing mechanism, and connect the pressurizing mechanism with the recovery mechanism;
[0054] Step 8: Use the pressure / volume controller 1 to pressurize the test solution into the test core through the outlet of the pure water / solution converter 2, with the water flow rate ranging from 0.01 to 1 mL / min. During the test, the water pressure changes are continuously recorded;
[0055] Step 9: Replace the liquid collection bottle 4 every 24 hours; shake the collected erosion liquid evenly, measure the turbidity, conductivity, and pH value, and then dry it at 105° C. to constant weight;
[0056] Step 10: When the turbidity of the corrosion liquid measured within 72 hours is less than 0.1 NTU, the test is considered to have reached equilibrium and the liquid injection is terminated; the air pressure in the sealed shell is reduced to atmospheric pressure and the sealed shell is opened;
[0057] Step 11: Open the core to measure the depth of bentonite squeezed into the cracks, and scan the crack surface morphology again to compare with that before the test;
[0058] The twelfth step is to analyze the relationship between water flow velocity, water pressure, crack morphology, the distance bentonite is squeezed into the crack, and the amount of erosion (i.e., the solid matter obtained by drying the erosion liquid collected every day to a constant weight, and calculating the total weight of the solid matter during the entire test process), so as to understand the sealing and anti-erosion performance parameters of sodium-based bentonite under the conditions of water erosion in granite cracks.
[0059] It should be noted that it is obvious to those skilled in the art that the present invention is not limited to the details of the above exemplary embodiments, and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims are included in the present invention, and any figure mark in the claims should not be regarded as limiting the claims involved.
[0060] The present specification uses specific examples to illustrate the principles and implementation methods of the present invention. The above examples are only used to help understand the method and core idea of the present invention. At the same time, for those skilled in the art, according to the idea of the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as limiting the present invention.
Claims
1. A device for studying the influence of surrounding rock fissure water on the erosion process of buffer materials, characterized in that: It comprises a pressure / volume controller, a pure water / solution converter, a test core, a pressurizing structure and a recovery structure; a buffer material sample is arranged in the test core, the test core is arranged in the pressurizing structure, one end of the pure water / solution converter is connected to the pressure / volume controller, the other end of the pure water / solution converter is connected to one end of the test core, and the recovery structure is used to recover the solution flowing out of the other end of the test core; The pure water / solution converter includes a top cover, a base, a water tank and a water-proof membrane; the water tank is arranged between the top cover and the base, the water-proof membrane is arranged in the middle of the water tank, the top cover is provided with an exhaust hole and a water outlet hole, the base is provided with a water inlet hole, the water inlet hole is connected to the pressure / volume controller, and the water outlet hole is connected to the test core.
2. The device for studying the influence of surrounding rock fissure water on the erosion process of buffer materials according to claim 1 is characterized in that: The test core includes rock, a block, a permeable pad and a sealing sleeve; a crack with a known opening is arranged at one end of the rock, and a hollow cavity is arranged at the other end of the rock, the crack is connected to the hollow cavity, the buffer material sample is arranged in the hollow cavity, and the block is arranged at the end of the hollow cavity away from the crack; a permeable pad is arranged at each end of the rock, and the sealing sleeve is arranged outside the rock; one end of the pure water / solution converter is connected to the permeable pad close to the block; the recovery structure is connected to the permeable pad close to the crack.
3. The device for studying the influence of surrounding rock fissure water on the erosion process of buffer materials according to claim 1 is characterized in that: The pressurization structure includes a sealed shell, an air supply mechanism, a left base and a right base; the left base is arranged on the left side wall inside the sealed shell, and the right base is connected to the left base by bolts; the test core is arranged between the left base and the right base; the air supply mechanism is connected to the inside of the sealed shell.
4. The device for studying the influence of surrounding rock fissure water on the erosion process of buffer materials according to claim 3 is characterized in that: The sealed housing is provided with a pressure gauge.
5. The device for studying the influence of surrounding rock fissure water on the erosion process of buffer materials according to claim 3 is characterized in that: The sealing shell is provided with a safety valve.
6. The device for studying the influence of surrounding rock fissure water on the erosion process of buffer materials according to claim 3, characterized in that: The gas supply mechanism comprises a nitrogen cylinder.
7. The device for studying the influence of surrounding rock fissure water on the erosion process of buffer materials according to claim 1, characterized in that: The buffer material sample is a sodium bentonite block with a water content of 15% and a density of 1.6 g / cm 3 .
8. The device for studying the influence of surrounding rock fissure water on the erosion process of buffer materials according to claim 1, characterized in that: The recovery structure comprises a liquid collecting bottle.
9. The method for studying the influence of surrounding rock fissure water on the erosion process of buffer materials according to any one of claims 1 to 8, characterized in that: The main steps include: The first step is to select a granite core with obvious cracks running through it along the length, cut off 10 cm, and drill a hole from one end with a diameter of 3 cm and a depth of 6.5 cm; or, select a complete core, cut off 10 cm, drill a φ3 cm × 6.5 cm hollow cavity in the middle, and then cut it into two identical parts along the length; In the second step, a 3D laser scanner is used to obtain the surface morphology of natural / artificial fractures; The third step is to weigh sodium bentonite powder with a water content of 15%, and use a special compaction mold on a press to prepare a φ3cm×33cm cylindrical bentonite block with a dry density of 1.6g / cm; put the bentonite block into the hollow cavity in the core, and use a granite block to fill the gap above the core; Step 4: Open the sealing shell, put the sealing sleeve on the outer surface of the core, and use cable ties to fix the two ends of the sealing sleeve to the top of the left base and the right base; fix the left base and the right base to the test chamber with stainless steel bolts; assemble the sealing shell and seal it; The fifth step is to connect the air supply mechanism and the sealing shell, inflate and check the airtightness of the connecting pipeline and the sealing shell. If leakage is found, it should be dealt with in time; increase the air pressure inside the sealing shell to no less than 4000kPa, so that the sealing sleeve is close to the outer surface of the rock; Step 6. Open the vent of the pure water / solution converter, use a peristaltic pump or syringe to inject the test solution into the upper water tank through the water outlet until the test solution overflows the vent, and then close the vent. Step 7: operate the pressure / volume controller to absorb pure water, connect the pressure / volume controller, the pure water solution converter, the pressurizing mechanism, and connect the pressurizing mechanism with the recovery mechanism; Step 8: Use a pressure / volume controller to pressurize the test solution into the test core through the outlet of the pure water / solution converter, with the water flow rate ranging from 0.01 to 1 mL / min; continuously record the water pressure changes during the test; Step 9: Replace the liquid collection bottle every 24 hours; shake the collected erosion liquid evenly, measure the turbidity, conductivity, and pH value, and then dry it at 105°C to constant weight; Step 10: When the turbidity of the corrosion liquid measured within 72 hours is less than 0.1 NTU, the test is considered to have reached equilibrium and the liquid injection is terminated; the air pressure in the sealed shell is reduced to atmospheric pressure and the sealed shell is opened; Step 11: Open the core to measure the depth of bentonite squeezed into the cracks, and scan the crack surface morphology again to compare with that before the test; The twelfth step is to analyze the relationship between water flow velocity, water pressure, crack morphology and the distance and erosion amount of bentonite squeezed into the crack, so as to understand the sealing and anti-erosion performance of sodium-based bentonite under the conditions of water erosion in granite cracks.
Citation Information
Patent Citations
Device for researching influence of surrounding rock crack water on buffer material erosion process
CN214174111U